Fractional CO2 laser is as effective as pulsed dye laser for the treatment of hypertrophic scars. (18th August 2021) - Radmanesh, Mohammad; Mehramiri, Samira; Radmanesh, Ramin
Abstract: Background: Both pulsed dye laser (PDL) and fractional CO2 laser (FCO2 L) are used commonly for the treatment of hypertrophic scars. Objective: To compare the efficacy of PDL and FCO2 L on hypertrophic scars. Patients and methods: One part of each scar, or one of the two similar scars in 35 patients was treated with PDL and the other parts, or scars were treated with FCO2 L. The parameters used for FCO2 L were: power = 30 W, pulse energy = 50 mJ, density = 200 spots/cm 2 . The parameters used for 585 nm PDL were 9 J/cm 2 with 5 mm spot size. The FCO2 L side was treated for three passes to debulk the scar. The coagulated tissue was wiped out before the next pass. The PDL side was treated with two superimposed passes. The procedures were repeated every month for 4 months. Results: After four sessions of laser therapy, both sides showed remarkable improvement but no meaningful difference was detected between two areas that were treated with PDL and FCO2 Ls ( p  > .05). The mean Vancouver Scar Scale was 7.31 ± 1.93 in the beginning and 4.26 ± 1.48 for FCO2 L and 4.33 ± 1.70 for PDL one months after the final session. Conclusions: Both PDL and FCO2 Ls were equally effective on hypertrophic scars.